Regional energy futures as decision support in the transition to net zero emissions: North of Tyne case study. Issue 6 (3rd June 2022) - Copeland, Claire; MacKerron, Gordon; Foxon, Timothy J.
ABSTRACT: Futures studies can fulfil a variety of purposes; for informing policy, developing investment or business strategies, and changing perceptions of what the future may hold. Futures can therefore be described as having transformative potential. This paper uses a participatory scenario approach to develop regional energy futures for a U.K. case study in the North of Tyne region. Two sets of futures are developed; pre-pandemic, and during the pandemic. This was for insights into the challenges for developing subnational scale futures, and how futures thinking may have been impacted by the pandemic. The North of Tyne energy future scenarios are based on discussions in two facilitated stakeholder workshops, pre and during the pandemic. It was found that the pandemic had resulted in shifts in practices and behaviours such as increased home working, and an appreciation of local environments and communities. However, there were commonalities too. In both settings, decarbonisation was a strong driver for change in the energy system, as was the need for fairness in the transition. There were barriers in futures thinking that had to be overcome, most notably was the presumption that meeting the net zero target was a certainty. This presented difficulties in imagining futures that didn't achieve this target or did so but more slowly. The importance of being able to imagine living in all kinds of future worlds will be critical in a system undergoing such profound change so that strategic foresight is developed to minimise risks of missing the net zero target.